THE ROLE OF SOCIAL MEDIA THROUGH PROMOTION AS ITS MEDIATING VARIABLE IN AFFECTING CONSUMERS’ PURCHASE DECISIONS (RESEARCH ON SOCIAL MEDIA FOLLOWERS OF ESENAK BUBBLE TEA KARAWANG) - Abdul Jabbar; Chaerudin Chaerudin (Dinasti International Journal of Education Management And Social Science, 2021)
Changes in spending style caused by economic progress are a phenomenon that should be learned so that business people will continue to keep up with recent developments, particularly on the marketing field along with technological advances, these marketing methods which start modernized by latest technology, just like social media is an example. This research aims to reveal the impact from social media with promotion as mediation on purchasing decisions at bubble tea store eSenak Karawang. The research method used was descriptive verification with a quantitative technique. The population in this research are the total number of eSenak followers with sample of 175 respondents. Data were evaluated through path analysis by multivariate data techniques to examined the hypothesis. The results of this research declared that social media has a positive affect on promotion, social media has no affect on purchasing decisions, promotions have an affect on purchasing decisions.